The Effect of Communication and Industrial Relations on Employee Job Satisfaction at PTPN VII Unit Tebenan - Dwi Ervina; Dina Mellita (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of the research is to know the analysis of the impact of communication, as well as industrial relations on employee job satisfaction, and their effect on employee job satisfaction. The tentative assumption put forward is that communication has a significant effect on employee job satisfaction and there is a significant influence of industrial linkages on employee job satisfaction. It is evident from the research results that communication and industrial relations have a significant relationship with employee job satisfaction. In this research, it is proven that the most influential on employee job satisfaction is communication.